The mediating role of academic self-efficacy in the relationship between university students' heutagogical competencies and lifelong learning tendencies - Akçay, Püren (Frontiers in Education, 2025)
IntroductionThis study investigates the role of academic self-efficacy in the relationship between university students' heutagogical skills and their lifelong learning tendencies. Positioned as the missing link long sought in the literature, the study highlights how academic self-efficacy facilitates the transition from heutagogical competence to lifelong learning, offering a significant contribution to existing mediation research.MethodsData were collected from 545 students enrolled at a private university in Istanbul during the 2024–2025 academic year. The analyses were conducted using structural equation modeling. The measurement tools included the Lifelong Learning Attitude Scale, the Self-Determined Learning (Heutagogy) Skills Scale, and the Academic Self-Efficacy Scale.ResultsThe findings revealed that Heutagogical Competence significantly predicts Lifelong Learning Tendency both directly and indirectly through Academic Self-Efficacy, demonstrating a partial mediation effect. Academic Self-Efficacy functions as an important mechanism linking heutagogical competence to lifelong learning, while Heutagogical Competence also maintains its direct influence.DiscussionThese results indicate that supporting students' academic self-efficacy is crucial for strengthening heutagogy–based learning processes in educational environments. The study contributes to the literature by uncovering a new mechanism within the heutagogical competence-academic self-efficacy–lifelong learning pathway and clarifying that this mediation is partial rather than complete.